ENVIRONMENTAL POLLUTION IN THE CITY OF BUCHAREST - IONELA-MIHAELA ROȘU MARIN; GABRIEL CIUIU; COSMIN JINESCU; VALI-IFIGENIA NICOLOF (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The work covers air quality monitoring tools in Bucharest, major industrial facilities impacting pollution and the city's eight air quality monitoring stations. Data on pollutant emissions from Bucharest's thermal power plants (SO2, NOx and dust) are presented. Finally, the paper graphically presents the annual average concentrations of NO2, SO2, PM10 and O3 at the monitoring stations and examines pollution peaks and daily limit exceedances from 2017 to 2022.